Features of Postpositions in Chulym Language - F. Başbuğ (Научный диалог, 2017)
The article considers several postpositions in Chulym as compared with other Turkic languages. It is noted that despite the fact that their functions have similarities with those of nominal cases, their functional scope is much wider. The author emphasizes that postpositions play an auxiliary role: they are used together with independent words to express grammatical meaning of case endings, and also help to establish semantic relations between lexical words in a sentence. It is shown that postpositions are able to express meanings of place, direction, instrument, reason, etc. It is noted that in traditional Turkic studies postpositions are recognized as uninflected words. The author’s study of postpositional constructions in Chulym language is presented. Special attention is paid to semantic derivation, by which the postposition is formed. Semantic and grammatical links of postpositions within the structure of phrases and sentences are demonstrated on examples of a number of postpositions ( шили, öжин, зäй, -бле etc.).